Infusion of chimeric antigen receptor T cells against dual targets of CD19 and B-cell maturation antigen for the treatment of refractory multiple myeloma. Issue 1 (January 2020) - Tang, Fang; Lu, Yin; Ge, Yongqin; Shang, Jingjing; Zhu, Xiaming
Objective: To investigate the safety and efficacy of chimeric antigen receptor T (CAR-T) cell infusion in patients with refractory multiple myeloma (MM). Methods: Sixteen patients diagnosed with refractory MM were included in this study. Patients received initial infusions of T-derived CD19/B-cell maturation antigen (BCMA) CAR-T cells with 100% CD19, followed by second infusions with 40% BCMA and third infusions with 60% BCMA. The total doses were 0.5–1 × 10 7 /kg CD19 and 1.2 − 6.2 × 10 7 /kg BCMA. Patients were monitored after infusion. Levels of interleukin (IL)-2, IL-6, IL-10, tumor necrosis factor-α, and C-reactive protein were determined by enzyme-linked immunosorbent assay. Results: Cytokine release syndrome (CRS) was observed in all 16 patients. Thirteen patients with CRS stage II−IV had persistent hyperthermia from 5−14 days after infusion, while most patients developed hyperthermia from 1 day after infusion and their temperatures returned to normal within 2−10 days. Levels of all factors were significantly elevated 2 days after infusion, peaked at 5 days, and then gradually decreased to normal levels. All inflammatory factors showed normal levels by 10 days after infusion. Conclusion: Body temperature and levels of inflammatory factors all increased dramatically after infusion of CD19/BCMA CAR-T cells, but recovered to normal levels after appropriate treatment and nursing.